Active film incorporated with clove essential oil on storage of banana varieties. Issue 5 (9th September 2019) - Alves de Figueiredo Sousa, Heloísa; Gonçalves de Oliveira Filho, Josemar; Egea, Mariana Buranelo; Rosa da Silva, Edilsa; Macagnan, Dirceu; Pires, Marcio; Peixoto, José
Abstract : Purpose: Banana is an important tropical fruit with high demand in the market. The ripe fruits are less resistant to transport making logistics difficult. Moreover, as a climacteric fruit, it has a short post-harvest shelf life. Edible coatings/films, including active substances, have been used as an alternative for preserving fruits and vegetables during post-harvest period. The purpose of this study was to evaluate the incorporating clove essential oil on the properties of cassava starch films and their effect on the post-harvest quality of different banana varieties. Design/methodology/approach: Cassava starch films incorporating clove essential oil were developed and the films were characterized with respect to moisture, thickness, solubility, water vapor permeability (WVP), biodegradability, color and in vitro antifungal activity. Cultivars such as Prata-Anã, Grand Nine, BRS Tropical and BRS Conquista were coated with cassava starch, cassava starch film with clove essential oil (CSEO) and polyvinyl polychloride (PVC). The quality of fruits was monitored during eight storage days using mass loss, total soluble solids content (TSS) and titratable acidity (TTA). Findings: Incorporation of clove essential oil significantly increased film thickness, reduced moisture content, solubility and WVP ( p < 0.05) and did not affect the biodegradability and color of the films. The essential oil incorporated films showed antifungal activity against the fungi Colletotrichum gloeosporioides and Colletotrichum musae, but not against the yeast Saccharomyces bourladii . CSEO and PVC coating were more efficient in reducing the mass loss, SS content and TTA of the coated fruits in all varieties studied. Both CSEO and PVC coatings improve the quality attributes such as TSS and TTA and reduced mass loss, of the banana varieties such as Prata-Anã, Grand Nine, BRS Tropical and BRS Conquista during storage. Originality/value: The active film with essential oil showed antifungal activity and essential oil can be incorporated into other food systems. This study approaches a new possibility of film coating with essential oil for a banana that showed minimum weight loss and satisfactory quality and increased shelf life. This film coating demonstrates biodegradable characteristics that could be eco-friendly and sustainable to consumers.